Awareness of Economic, Environmental, and Social Issues and Financial Soundness–Does The Covid-19 Pandemic Matter? - Hasan Mukhibad; Bayu Bagas Hapsoro (Universitas Negeri Semarang, 2023)
Purpose : Regulators, the public and researchers emphasize the business world to increase awareness of economic, environmental, and social issues as corporate social responsibility (CSR). However, the economic consequences of CSR are still being debated. This study proves the role of CSR disclosure on financial soundness and the role of the coronavirus disease (covid-19 pandemic) in the relationship between the two. Method : The research sample is a manufacturing company listed on the Indonesia Stock Exchange, with observations from 2015 to 2021. Data analysis uses panel data regression. Findings : The results showed that CSR disclosure does not affect financial soundness, but the interaction between CSR and covid-19 pandemic negatively affects financial soundness. Therefore, covid-19 pandemic plays a major role in the extent to which CSR affects financial soundness. We will conduct regression analysis with other indicators of financial soundness to assess the robustness of our findings. Novelty : The study contributes to the expansion of the prior literature in two important ways. First, we use the financial soundness consequences of CSR disclosures. This study provided evidence of covid-19’s effect on CSR disclosures. Keywords : Customer Loyalty; Environmental Concern; Risk, Covid-19 Pandemic